European Union Support for Colombia's Peace Process Civil Society, Human Rights and Territorial Peace - Pérez de Armiño, Karlos (Rethinking Peace and Conflict Studies, 2023)
This open access book provides a comprehensive analysis of the EU's crucial support for the implementation of the Havana Peace Agreement between the Colombian government and the FARC-EP. It explores the use of new approaches and instruments that, despite some limitations and criticisms, could go beyond conventional liberal peace and provide useful lessons. Particular attention is paid to three axes: strengthening civil society, protection of human rights and a territorial peace perspective, as a contribution to the "local turn" in peace policies. The book first outlines the background of the conflict, the EU's two-decade defense of a negotiated peace, and the complexities of the peace process. Then, it analyses the development cooperation and political support provided in different areas: the collective reinsertion of ex-guerrillas, women and gender initiatives, the rights of ethnic communities, the sophisticated transitional justice system, as well as activities on reconciliation, victims and protection of human rights defenders.